Kesalahan Mahasiswa PGSD UTM dalam Menyelesaikan Sistem Persamaan Linier Tiga Variabel Berbentuk Soal Cerita - Ariesta Kartika Sari (Widyagogik)
This paper describes the errors of the research subjects in solving Linear Equation System (LES) with three variables in form of narration. The errors that the students made in solving this mathematical problem hopefully can be used as one of the considerations in deciding the learning method or improving the learning. This paper is an exploratory descriptive paper. The research subjects are PGSD department students of University Trunojoyo Madura even semester of academic year 2011-2012  as many as 52 students. The data analysis is done in three stages, which are: (a) data reduction, (b) data presentation, and (c) inference. The research results indicate some errors done by the students are as follow: (a) errors in creating mathematical models; (b) errors in inscribing determinant method formulas; (c) errors in inputting data into the determinant method formulas; (d) errors in calculating using determinant method; and (e) errors in the actual problem solving stage.